Unveiling the Dynamics of Job Satisfaction and Job Switching Decisions through the Lens of Glass Ceiling Factors: An Empirical Study of Women in Khyber Pakhtunkhwa’s Private Banking Sector - Najia Aman; Fayaz Ali Shah; Shahid Jan Kakakhel (Dialogue Social Science Review (DSSR), 2025)
This study investigates the challenges faced by women in the private banking sector of Khyber Pakhtunkhwa (KP), focusing on the interplay between glass ceiling factors, job satisfaction, and job-switching decisions. A sample of 280 women banking professionals, including account opening representatives, customer service representatives, managers, and officers, was surveyed using validated scales adapted from existing literature to reflect the unique cultural and organizational dynamics of KP's banking sector. The findings reveal a significant negative relationship between glass ceiling factors—such as gender discrimination, unequal pay, and limited career development opportunities—and job satisfaction among women. These systemic barriers not only diminish professional engagement but also contribute to psychological stress and high turnover intentions. Job satisfaction emerged as a critical mediating factor, highlighting its role in mitigating workplace discrimination and structural inequalities. Organizational support policies, such as flexible work arrangements, maternity leave, and childcare facilities, were identified as effective interventions to counteract these challenges. The study underscores the urgent need for systemic reforms within KP's banking institutions to enhance job satisfaction, reduce turnover, and promote gender equality. The findings provide actionable insights for policymakers, banking institutions, and human resource practitioners to create equitable and supportive workplaces that empower women to achieve their full potential.